Us and them : perceptions of Chinese Singaporean undergraduates about the socio-cultural differences of foreign talents, the Singaporean identity and the impact of foreign talents on the Singaporean identity - Yeo Han Qi (2015)
Amidst the growing controversy surrounding Singapore's foreign talent policy, this paper examines the perceptions of Chinese Singaporean undergraduates on whether and how foreign talents are socio-culturally different, the Singaporean identity, and the impact of foreign talents on the Singaporean identity. Using surveys and interviews, it is found that most Chinese Singaporean undergraduates perceive foreign talents to be socio-culturally different, and believe in a distinct Singaporean identity that takes the form of being born and raised in Singapore, being unequivocally loyal to Singapore, possessing good Singaporean cultural knowledge, embracing multiculturalism, and behaving according to Singaporean cultural norms. To Chinese Singaporean undergraduates, the foreign talent inflow both strengthens and confounds the Singaporean identity. Taken together, the findings elucidate that the identity conceptions of Chinese Singaporean undergraduates amidst a rising foreign talent presence are primarily based on 'in-group/out-group' categorisations that strive to accentuate the positive distinctiveness of the 'in-group' — 'born and raised' Singaporeans.